Analysis of the Readiness for the Implementation of Electronic Medical Records at Faga Husada General Hospital - La Baha, Yusmina; Muzuh , Mega Ermasari; Sinta , Niska Salsiani (International Journal of Multidisciplinary Learners, 2025)
Faga Husada General Hospital plans to transition to electronic medical records (EMRs), requiring a preparation assessment. According to the Ministry of Health Regulation No.24 of 2022, all healthcare facilities must implement EMRs. The regulation mandates that every healthcare facility in Indonesia manage electronic medical records, with the transition process to be completed by December 31, 2023. This study aims to assess the hospital's readiness for implementing EMRs. The research conducted is descriptive quantitative with a cross-sectional approach, using the DOQ-IT (Doctor's Office Quality-Information Technology) tool. The sample size is 8 participants, and data were collected via a questionnaire. The analysis of readiness for EMR implementation using the DOQ-IT method assessed four variables: organizational culture preparedness, governance and leadership, human resources, and infrastructure. The results showed that organizational culture preparedness scored an average of 33, placing it in the "very prepared" category. Governance and leadership scored 33.12, human resources scored 32.8, and infrastructure scored 32.4, all also in the "very prepared" category. Overall, the hospital's readiness for EMR implementation is classified as very high, indicating that Faga Husada General Hospital is well-prepared for the transition